Characterization of planar flaws by synthetic focusing of sound beam using linear arrays. (April 2015) - Nanekar, Paritosh; Kumar, Anish; Jayakumar, T.
Abstract: Characterization of planar flaws by non-destructive evaluation is crucial from the point of view of structural integrity assessment. An approach involving SAFT processing of B-scan image collected by electronic scanning using linear array has been used for detection and characterization of planar flaws. The study was carried out on stainless steel plate with slots inclined at various orientations and carbon steel plates having implanted weld planar flaws. The results of these investigations are presented in this paper.